Corrosion inhibition behaviour of pyrrole and pyridine with the presence of oxygen scavenger / Ezan Suhailah Mohd Kassim - Mohd Kassim, Ezan Suhailah (2018)
Carbon steel finds wide application in a broad field of industries as a material of construction. However, in the presence of the neutral chloride media, they are more exposed to corrosion activity. To overcome this problem, organic-based inhibitor should be added as a protection against internal corrosion carbon steel. In this study, two main organic-based inhibitors, which are pyrrole and pyridine, were added into the solution to improve the inhibition efficiency.